2022
DOI: 10.1002/adma.202200337
|View full text |Cite
|
Sign up to set email alerts
|

Theory‐Guided Material Design Enabling High‐Performance Multifunctional Semitransparent Organic Photovoltaics without Optical Modulations

Abstract: Semitransparent organic photovoltaics (ST‐OPVs) have drawn great attention for promising applications in building‐integrated photovoltaics, providing additional power generation for daily use. A previously proposed strategy, “complementary NIR absorption,” is widely applied for high‐performance ST‐OPVs. However, rational material design toward high performance has not been achieved. In this work, an external quantum efficiency (EQE) model describing this strategy is developed to explore the full potential of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 64 publications
2
45
0
Order By: Relevance
“…Meanwhile, the ST-OSC device achieves a decent PCE of 6.15%, accompanied by an average visible transmittance (AVT) of 38.79%. Notably, Zhu et al reported a similar molecule ATT-9 exhibiting a PCE of 9.37% and an AVT of 35.5% while we were preparing this paper . Furthermore, the OPD device based on PTB7-Th:BFIC delivers an impressive specific detectivity of over 10 13 Jones in a broad spectrum ranging from 330 to 1030 nm …”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…Meanwhile, the ST-OSC device achieves a decent PCE of 6.15%, accompanied by an average visible transmittance (AVT) of 38.79%. Notably, Zhu et al reported a similar molecule ATT-9 exhibiting a PCE of 9.37% and an AVT of 35.5% while we were preparing this paper . Furthermore, the OPD device based on PTB7-Th:BFIC delivers an impressive specific detectivity of over 10 13 Jones in a broad spectrum ranging from 330 to 1030 nm …”
Section: Introductionmentioning
confidence: 73%
“…The relatively high charge mobility is conducive to reducing space charge accumulation and thus facilitating efficient charge extraction, consequently leading to the high FF of the relevant OSC . Eventually, the BFIC-based device achieves over 10% PCE, which is one of only a few examples of OSCs fabricated by ultranarrow band-gap organic semiconductors. ,,,, …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, alkylthio thiophene π-bridged ACS8 (ITIC derivative) and thieno[3,4- b ]thiophene π-bridged ATT-9 (Y6 derivative) have recorded an impressive J SC of up to 25.3 and 30.0 mA cm −2 , respectively. 15,16 However, the consequent high-level highest occupied molecular orbital (HOMO) and low-lying lowest unoccupied molecular orbital (LUMO) levels not only limit the utilization of donor materials, but also reduce the open-circuit voltages ( V OC ) of the resultant OSCs. Another outcome that should be particularly noted is that the π-bridge segment could give rise to two opposite impacts on intermolecular stacking, that is, the unfavorable irregularity induced by rotatable σ-bonds and favorable extension of π-conjugated planes.…”
Section: Introductionmentioning
confidence: 99%
“…Promising developments have been made in organic solar cells (OSCs) in recent years, with the power conversion efficiency (PCE) of the best devices exceeding 18%. The high PCE of this photovoltaic (PV) technology, together with other benefits such as flexibility, color tunability, and easy fabrication, contributes to its market competitiveness. On the other hand, the scalability and cost management of material synthesis and device production are the next issues to solve in order achieve wide-scale commercialization. To evaluate the cost components related to chemical synthesis, researchers in the field have proposed several concepts, such as synthetic complexity (SC), scalability factor (SF), and figure of merit (FoM). …”
mentioning
confidence: 99%